Life cycle assessment on the palm-based polyol production / Noorazah Zolkarnain - Noorazah , Zolkarnain (2015)
The search for renewable resources as a feedstock in the polyol production inspired polyol makers to expand their focus on vegetable-based feedstock rather than just concentrating on petroleum-based feedstock only. Currently, there are a few comprehensive studies on polyol production from palm oil as a feedstock. Palm-based polyol has been proven to have similar or even better characteristic and performance than petroleum-based polyol by several polyol manufacturers. This study is intended to evaluate and identify the environmental impacts from the production of palm-based polyol carried out in MPOB Polyol Pilot Plant through four different scenarios studies. The outcome from this study is important to support the use of renewable raw material in the production of bio-based polyol, and hence will further boost the application of palm oil and its derivatives. The ‘cradle-to-gate’ system boundary utilizing the LCA methodology for the production of palm-based polyol shows that the most significant impact from the production comes from the energy use at the polyol plant. This impact is mainly contributed by the use of electricity and productions of hydrogen peroxide. There are also impact contribution from palm-based products which were used as a feedstock during the production. The result obtained from the alternative scenario (Scenario 2), indicated a reduction of around 63-65% of the GHG emissions produced from the overall palm-based polyol production. There is not much difference on impacts and GHG values if glycerol is use to replace diol during the alcoholysis stage as in Scenario 3. However, the results at the pilot plant study will be more interesting if future work can be carried out at a commercial plant with larger scale production.